Analisis Sistem Informasi Akuntansi Penerimaan Dan Pengeluaran Kas Terhadap Sistem Pengendalian Internal Kas Pada PT. Bulan Biru Tour And Travel - Dinda Kama Dita; Tantina Haryati (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
A company needs an internal control system because to maintain the existence of cash appropriately for managing and controlling cash, one of which is cash receipts and cash disbursements. In this case, cash is the company's most liquid asset or asset and is prone to fraud, fraud and theft. In this study, the objective is to find out how the accounting information system for cash receipts and payments on the internal control system at PT. Bulan Biru Tour and Travel. This type of research is a type of case study research using a qualitative approach. Internal cash control in the company is inadequate, this is reflected in the implementation of internal cash control, there is an organizational structure in which there is a description of the duties and responsibilities of each part of the company, the authorization of the authorized official for each transaction of cash receipts and disbursements of the company. It is suggested that there should be a separation of duties between the recording function and the cash storage function.